Immediate Results of Omentopexy in Perforated Duodenal Ulcer: A Study of 186 Cases - Nishikant Gujar*, Jilani Awati, Sajid Mudhol, Salahuddin Contractor, Ravikumar Choudhari and Sushila Garag (Al Ameen Medical College, 2012)
Aim of the Study: The study was conducted to determine short term results in view of associated diseases, complications, mortality and hospital stay in patients with duodenal ulcer perforation treated by omentopexy. Main Findings: Age of patients range from 15 to 85 years; mean age was 45.58 years; In all cases, perforation was present on the anterior surface of the first part of the duodenum. Size of perforation varied from 0.3 to 2.5 cm. 50 (26.88%) patients had co-existing illnesses. Among the complications, the commonest complication was wound infection. 53 patients (28.49%) had wound infection, 45 patients (24.19%) had lung infections, 5 patients (2.68%) had re-perforation of the ulcer, 2 patients (1.07%) had burst abdomens, 2 patients (1.07%) had pelvic abscesses and 1 patient (0.53%) had DIC. Mortality was 18 patients(9.67%). Median hospital stay was 10 days. Conclusion: Perforation is one of the most catastrophic complications of peptic ulcer. In spite of modern advances in surgical, anesthetic and ancillary facilities, it still assumes life threatening dimensions. Omentopexy is a simple and safe procedure. The most important factors predisposing to complications are delay in admission to the hospital, associated diseases and shock on admission. Mortality and morbidity can be reduced by early admission, prompt resuscitation, treatment of associated diseases, early surgical intervention and prophylaxis of complications.